(untitled) (Brazilian Journal of Radiation Sciences, 2018)
In the care of people injured with wounds with incorporated radioactive material, the basic information is collected, using appropriate detectors, following procedures established in first aid protocol. The reliability of the data collected for medical treatment depends greatly on the metrological performance of the equipment, the experimental set up and the scenario of the occurrence of the accident. The methodology to evaluate the performance of the detectors use the comparison of the attenuation coefficient value of each radionuclide obtained by the attenuation curve of tissue-equivalent material to the theoretical value established by NIST in each experimental set up. The good performance was defined when the difference between the experimental and theoretical value is close to zero. The experimental set ups were chosen according to the types of possible measurements performed in the various scenarios of the radiological accident. The detectors used were Personal Radiation Dosimeter, IdentiFINDER2, Cadmium Telluride and Hyper Pure Germanium. The results for 241Am showed better performance with HPGe and IdentiFINDER2 shielded. For the 60Co the best performance occurred with the shielded and collimated IdentiFINDER2. For the 137Cs, the HPGe detector presented the best performance.